Prinsip Amicus Curiae terhadap Putusan Hakim dalam Perkara Pidana di Indonesia - Ksatria, Cokorda Agung Anuradha Darmaning (Ethics and Law Journal: Business and Notary, 2025)
The principle of Amicus Curiae or "Friend of the Court" is a legal concept that allows third parties to provide legal opinions to the court in a case, even though they are not directly involved. This principle has long been applied in the common law legal system, but is starting to be adopted in the civil law legal system, including in Indonesia. This research aims to understand the regulation of Amicus Curiae in the criminal justice system and its role in influencing judges' considerations in deciding cases in Indonesia. The method used is normative legal research with statutory, conceptual and comparative approaches. The research results show that even though it does not yet have an explicit legal basis in the Indonesian criminal justice system, Amicus Curiae has been used several times in important cases, such as the case of Prita Mulyasari and Richard Eliezer. The judge considers the opinion of the Amicus Curiae in the aspects of justice and social impact of a decision. In criminal procedural law, the existence of Amicus Curiae can enrich legal considerations with additional perspectives from experts or organizations that have an interest in the case. Even though it does not yet have strict regulations, Amicus Curiae is increasingly recognized as an important instrument in the Indonesian criminal justice system to achieve more objective and transparent justice. Further regulations are needed so that its use can be more optimal in the Indonesian legal system.